The Interaction of CtIP and Nbs1 Connects CDK and ATM to Regulate HR–Mediated Double-Strand Break Repair - Wang, Hailong (Public Library of Science, 2013)
CtIP plays an important role in homologous recombination (HR)–mediated DNA double-stranded break (DSB) repair and interacts with Nbs1 and BRCA1, which are linked to Nijmegen breakage syndrome (NBS) and familial breast cancer, respectively. We identified new CDK phosphorylation sites on CtIP and found that phosphorylation of these newly identified CDK sites induces association of CtIP with the N-terminus FHA and BRCT domains of Nbs1. We further showed that these CDK-dependent phosphorylation events are a prerequisite for ATM to phosphorylate CtIP upon DNA damage, which is important for end resection to activate HR by promoting recruitment of BLM and Exo1 to DSBs. Most notably, this CDK-dependent CtIP and Nbs1 interaction facilitates ATM to phosphorylate CtIP in a substrate-specific manner. These studies reveal one important mechanism to regulate cell-cycle-dependent activation of HR upon DNA damage by coupling CDK- and ATM-mediated phosphorylation of CtIP through modulating the interaction of CtIP with Nbs1, which significantly helps to understand how DSB repair is regulated in mammalian cells to maintain genome stability.